Geology of late-Variscan Sàrrabus pluton (south-eastern Sardinia, Italy). Issue 2 (1st December 2021) - Secchi, F.; Naitza, S.; Oggiano, G.; Cuccuru, S.; Puccini, A.; Conte, A. M.; Giovanardi, T.; Mazzucchelli, M.
ABSTRACT: This paper deals with the geological mapping of the late-Variscan Sàrrabus pluton, (south-eastern Sardinia), a shallow multiple and composite igneous complex dominated by several generations of granodiorites, metaluminous and peraluminous granites and repeated pulses of mantle-derived mafic magmas. The map has been compiled based on geological surveys at 1:10, 000 and 1:5, 000 scales, assisted by in situ gamma-ray spectrometry and detailed petrographic investigations. Granite-related ore deposits have been also reported. The emplacement age of the pluton can be constrained by U/Pb dating on zircons of Cala Regina granodiorite, yielding an age of 286 ± 9 Ma. The resulting scenario documents a bimodal magmatism controlled by an EW trending shear zone, followed by the shallower emplacement of several pulses of independent granite magmas.